COMMANDO in Locoregional Recurrence of Oropharyngeal Carcinoma / Abdul Azim Al-Abrar Ahmad Kailani ... [et al.] - Al-Abrar Ahmad Kailani, Abdul Azim; Khalid, Ahmad Kusyairi; Mohamad Yunus, Mohd Razif; Mohamad, Irfan (Universiti Teknologi MARA Cawangan Selangor, 2020)
Squamous cell carcinoma is the most common malignant neoplasm of the upper aerodigestive tract, and presentation is usually at the late stages when the diagnosis is made. Recurrence after 1st therapy is common especially in the locoregional area of the tumour. For cancers affecting the oral cavity, oropharynx, and mandible, “COMMANDO” (Combined Mandibulectomy and Neck Dissection Operation) is one of the surgical approaches which constitutes of primary tumour resection, mandibulectomy and neck dissection. We describe a case of rapid locoregional recurrence following 1st surgical procedure of bilateral tonsillectomy and extended neck dissection of oropharyngeal squamous cell carcinoma in a young healthy individual without history of alcohol and tobacco abuse involving the right buccal region which after positron emission tomography was done, showed involvement of right pterygoid muscles, right-sided tongue muscle, and right mandible. The patient underwent redo salvage surgery and reconstruction with anterolateral thigh flap.